2019
DOI: 10.33899/rjs.2019.163153
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Formaldehyde Treated Barley in Awassi Ewes Rations in Milk Production and some Chemical and Microbial Traits of Yogurt

Abstract: This study was conducted in research department of animal resource/ Al-Rashidiya, at ministry of agriculture by using 14 of genetically improved awassi ewes, average body weight 56.00 ± 2.10 kg and age ranged between 3-5 years. Ewes were allocated according to their weight and milk production into two groups. The first was control (T1), fed on ration consist mainly of untreated barley and contain 9.69% of degradable protein and 3.77% of undegradable protein as dry matter. The second group (T2) was fed on same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A series of experiments has been done to investigate the effect of chemical treatment of barley on milk production. Hassan et al, (12) reported that treatment of barley grain with formaldehyde significantly increased milk yield in Awassi Ewes. Similarly, Kassem et al (14) revealed that either barley, wheat or soybean meal fed lactating sheep under pasture conditions have a significant effect on milk production.…”
Section: Introductionmentioning
confidence: 99%
“…A series of experiments has been done to investigate the effect of chemical treatment of barley on milk production. Hassan et al, (12) reported that treatment of barley grain with formaldehyde significantly increased milk yield in Awassi Ewes. Similarly, Kassem et al (14) revealed that either barley, wheat or soybean meal fed lactating sheep under pasture conditions have a significant effect on milk production.…”
Section: Introductionmentioning
confidence: 99%